If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(x + -4) = 8x + -28 Reorder the terms: 6(-4 + x) = 8x + -28 (-4 * 6 + x * 6) = 8x + -28 (-24 + 6x) = 8x + -28 Reorder the terms: -24 + 6x = -28 + 8x Solving -24 + 6x = -28 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. -24 + 6x + -8x = -28 + 8x + -8x Combine like terms: 6x + -8x = -2x -24 + -2x = -28 + 8x + -8x Combine like terms: 8x + -8x = 0 -24 + -2x = -28 + 0 -24 + -2x = -28 Add '24' to each side of the equation. -24 + 24 + -2x = -28 + 24 Combine like terms: -24 + 24 = 0 0 + -2x = -28 + 24 -2x = -28 + 24 Combine like terms: -28 + 24 = -4 -2x = -4 Divide each side by '-2'. x = 2 Simplifying x = 2
| 4*(x+1)=2*(5-3x) | | 6+3a= | | 7u-36=3(u-8) | | t^2-60t=-450 | | t^2+60t=-450 | | -3*-3+6+2= | | 14(6x+16)= | | 3*3+6+2= | | 5+7(2b-2b)=5 | | y(25+-.75y)=350 | | x^2+y^2+6x-14y+42=0 | | 42-21x=63-7y | | (6xy+7)dx+(3x^2-2)dy=0 | | 6x+9-x+19= | | 4x+10=-42-8x | | 3n=34 | | 17x-2x=7x+11 | | 7x+13=3x+65 | | 4x+38=180 | | 2(x-3)(x-3)+3=13 | | 2(x-3)+3=13 | | x^4-x^3-2x^2+4x-24=0 | | (X^2+24)= | | 3x^2-11x-3=-x^2 | | Un=5+(0.1n-0.1) | | Un=5+(0.1n+0.1) | | Cos(5x)-cos(9x)=0 | | z^2-(3-2i)z+(5-5i)=0 | | 6x=n+4 | | 4x^2+12x+9=49x | | 4x^3+12x+9=49x | | -6.8(7.9+1.2*-7.3)+3.7=4.2*-7.3+40.90016 |